2004
DOI: 10.1111/j.1464-410x.2004.05111.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dartos fascia and tunica vaginalis pedicle wrap for the tubularized incised plate in primary hypospadias repair

Abstract: were repaired in one of three hospitals over 3 years. All patients were repaired using the TIP technique, with dartos fascia wrap used in 20 and TVPW in 29, without using a loupe or microscope during surgery. Urinary diversion and splinting were provided by a urethral catheter. The operative duration for both groups was similar at ª 2 h. RESULTSIn the dartos fascia group there were three (15%) fistulae, but there were none in the TVPW group. CONCLUSIONSAlthough the dissection for TVPW seems to be cumbersome th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 13 publications
1
46
1
Order By: Relevance
“…Since Retik et al [18] first described the use of the preputial dartos flap as a barrier layer between the neourethra and the penile skin, it has been commonly used for prevention of urethrocutaneous fistula formation. External spermatic fascia flaps, tunica vaginalis and scrotal and ventral dartos flaps have been described as alternatives to the dorsal ones especially in circumcised boys or those undergoing reoperation [19,[22][23][24]. However, poorly developed ventral skins, insufficient flap formation and asymmetric flaps that can cause penile rotation were reported to be limiting factors.…”
Section: Discussionmentioning
confidence: 97%
“…Since Retik et al [18] first described the use of the preputial dartos flap as a barrier layer between the neourethra and the penile skin, it has been commonly used for prevention of urethrocutaneous fistula formation. External spermatic fascia flaps, tunica vaginalis and scrotal and ventral dartos flaps have been described as alternatives to the dorsal ones especially in circumcised boys or those undergoing reoperation [19,[22][23][24]. However, poorly developed ventral skins, insufficient flap formation and asymmetric flaps that can cause penile rotation were reported to be limiting factors.…”
Section: Discussionmentioning
confidence: 97%
“…Complications do occur after every hypospadias repair. Currently there is expected complication rate of 5–10% mostly fistulas in one stage urethroplasty [14] (Table 3). …”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al . [19] have prospectively compared the two techniques of neourethral coverage after a TIP procedure. They have concluded that TIP with TVF could be an alternative to other techniques in a primary case of hypospadias.…”
Section: Discussionmentioning
confidence: 99%